Kurikulum berbasis moral dan tujuan pendidikan Islam perspektif Harun Nasution - Sungkowo, Andri; Sehabudin, Encep; Dinata, Syaiful; Hatta, Hatta; Ernawan, Ayunda Silvia Dewi; Achmad, Fatoni (MAN 4 Kota Pekanbaru, 2025)
This study aims to analyze the objectives of Islamic education and its curriculum from Harun Nasution’s perspective using a library research method through books and scientific journals. The findings show that Harun Nasution’s thoughts on the Islamic education curriculum are progressive and systematic, emphasizing spiritual, moral, intellectual, and social harmony. He proposed a phased curriculum suited to students’ cognitive, emotional, and spiritual growth, beginning with introducing basic values and moral formation in early education and culminating in broader religious understanding and social responsibility at higher levels. The foundation of this curriculum lies in placing morality at the center, stressing that religious education is not merely knowledge transfer or ritual practice but should shape strong character and tolerance. Harun highlighted rationality, causality, and guidance from the Qur’an and Sunnah, rejecting fatalism. Its success depends on ideal educators knowledgeable, exemplary, and adaptive, capable of integrating spirituality, reason, and social competence to form holistic individuals relevant to modern challenges.